The exchange : after The firm [compact disc, unabridged] - Grisham, John (Random House Audio, 2023)
Fifteen years after they exposed the crimes of Memphis law firm Bendini, Lambert & Locke, Mitch and Abby McDeere are living in Manhattan, where Mitch is a partner at the largest law firm in the world. When a mentor in Rome asks him for a favor that will take him far from home, Mitch finds himself at the center of a sinister plot that has worldwide implications, and once again endangers his colleagues, friends, and family. Mitch has become a master at staying one step ahead of his adversaries, but this time there's nowhere to hide.